Special study on the productivity of Sahiwals and their crosses in Kenya - International Livestock Centre for Africa (International Livestock Centre for Africa, 1978)
Brief description of the objectives of ILCA special study concerning productivity of Sahiwals and their crossbreeds in Kenya.